Nb-doped Sr2Fe1.5Mo0.5O6-δ electrode with enhanced stability and electrochemical performance for symmetrical solid oxide fuel cells. Issue 12 (15th August 2019) - Gou, Manli; Ren, Rongzheng; Sun, Wang; Xu, Chunming; Meng, Xingguang; Wang, Zhenhua; Qiao, Jinshuo; Sun, Kening
Abstract: In this study, Nb doped double perovskite oxide (Sr2 Fe1.4 Nb0.1 Mo0.5 O6-δ ) is prepared and tested as symmetrical electrodes for intermediate temperature solid oxide fuel cells. X-ray diffraction demonstrates that Sr2 Fe1.4 Nb0.1 Mo0.5 O6-δ maintains more stable cubic perovskite phase structure than its raw material (Sr2 Fe1.5 Mo0.5 O6-δ ) under reducing atmosphere. X-ray photoelectron spectrometry shows that Nb doping significantly enhances bond strength of FeOFe(Nb) so that Fe ion maintains more stable oxidation states after reducing. At 600 °C, Nb doping also increases the conductivity from 17.62 to 27.61 cm −1 in air and from 11.11 S cm −1 to 15.86 S cm −1 in wet hydrogen (∼3% H2 O). Furthermore, Sr2 Fe1.4 Nb0.1 Mo0.5 O6-δ exhibits enhanced electrochemical performances in terms of lower polarization resistance under both oxidizing and reducing atmospheres. Peak power densities of 364.93 and 531.49 mW cm −2 at 750 and 800 °C are obtained based on a single symmetrical cell with Sr2 Fe1.4 Nb0.1 Mo0.5 O6-δ electrode, which also shows excellent redox stabilities. All of these results confirm that Sr2 Fe1.4 Nb0.1 Mo0.5 O6-δ electrode has promising prospects for the symmetrical intermediate temperature solid oxide fuel cells.